Exploring the Capability of Elementary School Teachers as Musical Conductors in Formal School Activities - Sri Hapsari Wijayanti; Yohanes Arianto Budi Nugroho; Vanessa Emmily Dirgantara; May Triyanti Manalu (Journal of Innovation and Community Engagement, 2023)
Leading a choir at official school events is one of the skills that a school teacher should have. School events attended by students or fellow teachers usually begin with singing songs together, such as in national ceremonies or other formal school activities. However, it turns out that not all teachers are confident and capable of being conductors when their role is needed. Teachers at Sekolah Dasar Negeri (SDN) Cicayur 1, a state-owned elementary school in Cisauk District, Tangerang Regency, have such experience. A community service activity has been carried out for three months, attended by all fifteen teachers at the school, including the principal, to explore and train the skills to become conductors for the teachers. Activity began with the preparation stage, coordinating with the school for smooth implementation. At the implementation stage, activities were carried out using lecture, demonstration, practice, and assignment methods. At the evaluation stage, the assignment result was reviewed from seven videos containing the teacher's performance while leading a song at a formal event as a conductor. The videos show that teachers still need more practice to do better, especially in terms of song expressivity, accuracy of song tempo, stability of song tempo, and tempo matching with music score. If teachers' abilities as conductors can be improved, in the future, it is expected that teachers will be able to teach students how to become professional conductors, and the school can consider organizing extracurricular activities for choirs.